1979
DOI: 10.1073/pnas.76.11.5475
|View full text |Cite
|
Sign up to set email alerts
|

Participation of guanine nucleotides in nucleation and elongation steps of microtubule assembly.

Abstract: Critical concentrations for formation of microtubules from subunits with GTP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
27
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 19 publications
5
27
0
Order By: Relevance
“…It was subsequently reported that GDP would permit the elongation of microtubule seeds, but not de novo polymerization (Carlier & Pantaloni, 1978;Karr et al, 1979). It was therefore suggested that nucleation required a triphosphate in the exchangeable site.…”
Section: Discussionmentioning
confidence: 99%
“…It was subsequently reported that GDP would permit the elongation of microtubule seeds, but not de novo polymerization (Carlier & Pantaloni, 1978;Karr et al, 1979). It was therefore suggested that nucleation required a triphosphate in the exchangeable site.…”
Section: Discussionmentioning
confidence: 99%
“…(7) What is the mechanism for regulation of adenylate cyclase by Mg2+ (Cech et al, 1981) and other divalent cations and for activation of the adenylate cyclase system by NaF? (8) Finally, does the ubiquitous association of GTP-binding proteins with the regulatory function of GTP hydrolysis (Caskey et al, 1972;Karr et al, 1979;Shinozawa et al, 1979) suggest that the adenylate-cyclase-coupled G-protein may represent a macromolecular cue that synchronizes hormonestimulation with other, apparently unrelated, cellular functions?…”
Section: Summary Offuture Questionsmentioning
confidence: 99%
“…GTP binds rapidly and reversably to one exchangeable binding site (E-site) per tubulin subunit (1). During microtubule assembly, the E-site GTP undergoes a hydrolysis step as the subunit adds (2-5); and the GDP that is formed remains tightly bound, nearly one per dimer, in the polymer (3,4,6 (7)(8)(9)(10) and, reportedly, GDP (10)], the necessity for a hydrolysis step during assembly has been unclear.Microtubules undergo a constant opposite-end assembly/ disassembly mechanism in vitro (6). At an apparent equilibrium state for the polymer, subunits add at one end [the net assembly or (A) end] at a rate that is greater than their rate of loss at this end.…”
mentioning
confidence: 99%
“…Because nucleotides that are incapable of 13- (7)(8)(9)(10) and, reportedly, GDP (10)], the necessity for a hydrolysis step during assembly has been unclear.…”
mentioning
confidence: 99%